The Role of Transgenic Livestock in the Treatment of Human Disease - Keefer, Carol L.; Pommer, Jerry; Robl, James M. (Council for Agricultural Science and Technology (CAST), 2007)
This paper describes the potential for transgenic livestock to advance the development of new medications for the treatment of human disease. Two techniques discussed in this paper are the predominant methods used to produce transgenic livestock, pronuclear microinjection and somatic cell nuclear transfer (SCNT). The paper offers a brief overview of current production methods and challenges and addresses economic, regulatory, and societal factors that impact the commercialization of products and treatments derived from transgenic animals. An appendix provides an in-depth description of the SCNT methodology.